The Effect of Yoga on Estrogen in Women of Fertile Age Experiencing Stress - Raharjo, Rahmawati; Wahyudi, Gufron (Pusat Penelitian dan Pengabdian Masyarakat STIKES Banyuwangi, 2025)
Women have the right to physical and mental health in order to be able to regulate and maintain fertility levels, and enjoy sexual life responsibly. However, women are very susceptible to stress, both working and non-working women. Where stressful conditions can affect reproductive health related to the hormonal function of the reproductive system. One alternative that can be used to reduce the impact of stress is by doing yoga. Yoga is thought to suppress cortisol secretion, where cortisol can cause estrogen imbalance through the activation mechanism of the HPA (Hypothalamus-Pituitary-Adrenal) axis and the HPO axis (Hypothalamus-Pituitary-Ovary). This study aims to analyze the effect of yoga on the estrogen hormone in women of childbearing age in the context of stress. The research design uses a posttest only control group design. Before the research began, the research team had received a certificate of Ethical Eligibility from the Health Research Ethics Commission of the Indonesian STRADA Institute of Health Sciences. The population in this study were WUS who were indicated to be stressed based on the DASS scale and had a normal menstrual cycle. Sampling uses purposive sampling. The sample in this study was 57 people who met the inclusion and exclusion criteria. The treatment group was given yoga 24 times with a duration of 60 minutes at each yoga session guided by a professional yoga instructor. Meanwhile, the control group did not receive any treatment, but was monitored every week to avoid samples dropping out. Based on the results of the Mann-Whitney test, it shows a p value of 0.000. This shows that there are differences in estrogen levels in the control group and the treatment group. Yoga is considered effective in maintaining estrogen concentrations within normal limits. In this case, especially in women of childbearing age with stressful conditions. Yoga can have a positive impact both mentally and physically and maintain the function of vital organs such as the reproductive organs in women.